1987
DOI: 10.1002/jae.3950020206
|View full text |Cite
|
Sign up to set email alerts
|

An empirical model of a household's choice of activities

Abstract: This paper analyses how households of school-age children choose to participate in the labour force, volunteer work, democratic assemblies, and child-related leisure activities. Contrary to previous studies, the model presented in this paper treats all of these household's choice of activities involving time allocation decisions as simultaneously determined. The empirical section uses qualitative data estimation techniques which permit a wide range of joint and interaction effects among the variables of the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…For example, Stiglitz et al [4], Waring [5], and Soupourmas and Ironmonger [6] concluded that traditional indicators such as GDP are insufficient measures of contemporary economic performance. These traditional indicators do not include values other than market production, such as volunteering, which has its own specific value, as noted by Sues and Wilson [7], Emanuele [8], Steinberg [9], Femida and Narasimhan [10], Brown [11], Ross [12] and Montmarquette and Monty [13]. According to Salamon et al [14], Colman [15], Soupourmas and Ironmonger [6] and Novák [16], the value of volunteerism is measurable and it is advisable to measure it.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Stiglitz et al [4], Waring [5], and Soupourmas and Ironmonger [6] concluded that traditional indicators such as GDP are insufficient measures of contemporary economic performance. These traditional indicators do not include values other than market production, such as volunteering, which has its own specific value, as noted by Sues and Wilson [7], Emanuele [8], Steinberg [9], Femida and Narasimhan [10], Brown [11], Ross [12] and Montmarquette and Monty [13]. According to Salamon et al [14], Colman [15], Soupourmas and Ironmonger [6] and Novák [16], the value of volunteerism is measurable and it is advisable to measure it.…”
Section: Introductionmentioning
confidence: 99%
“…We also determine the benefits and costs incurred by volunteers such as out-ofpocket expenses such as travel, child care, and opportunity cost. The opportunity cost of time is important, as volunteers have high levels of education (Montmarquette & Monty, 1987). Last, we discuss the contributions of volunteers and benefits to volunteers that are not easily monetized.…”
Section: Introductionmentioning
confidence: 99%